Surface crack growth simulation and residual life assessment of high-speed train axles based on extended finite element method. (April 2022) - Ji, Dongdong; Zhang, Jiwang; Yi, Kejian; Huang, Yichang; Lu, Qi; Zhang, Haonan
Highlights: The extended finite element method is used in the fracture mechanics simulation of EA4T axle steel specimen and full-scale axle. Numerical model is built considering residual stress and wheelset press-fitting. The effectiveness of the extended finite element method (XFEM) was verified by comparing the simulation and experimental results. The measured load spectrum was applied, and the NASGRO equation was used to calculate the residual life of the axle. Abstract: High-speed railway axles may be damaged during service or maintenance. Therefore, to ensure axle service safety, the residual life of damaged axles is necessary for an accurate assessment. In this study, a small-sized specimen was analyzed and the effectiveness of the extended finite element method (XFEM) was verified by comparing the simulation and test results. Subsequently, the residual life of the EA4T axle with an initial crack was evaluated using the XFEM, which is based on fracture mechanics, and the actual axle service load spectrum. The results show that the critical failure sizes for the residual life of the power axle and non-power axle were 7 and 4 mm, respectively, for a crack located in the middle of the axle body; in contrast, for a crack located in the arc transition of the wheel seat, the critical failure dimensions were 9 and 5 mm, respectively. Based on the NASGRO equation and considering the damage tolerance safety factor, the residual lives of the power axle for the two crack locations were estimated to be 1.3953 × 10 6 and 9.636 × 10 5 km, respectively, while those of the non-power axle were 2.095 × 10 6 and 1.2583 × 10 6 km, respectively. The results of this study can provide a reference for the axle non-destructive testing (NDT) period.